Explaining Variation in Organizational Identity Categorization - Hsu, Greta; Elsbach, Kimberly D. (Organization Science, 2013)
In explaining why constituent groups often vary in their perceptions of the most salient aspects of an organization’s identity, existing research has drawn, almost exclusively, on social identity research and self-enhancement motives. This research suggests that when different organizational identity categorizations are enhancing to some groups but not others, variation in organizational identity perceptions arises. In this paper, by contrast, we explore the role that unmotivated or “spontaneous” cognitions may play in influencing variation in constituents’ organizational identity categorizations. Based on data from a study of U.S. business school constituents, we develop a dual-path model through which both motivated and spontaneous processes influence the different organizational identity categorizations constituent groups find to be most salient. We discuss both the theoretical and practical implications of these findings.